Causes of Postponement of Pediatric Surgical Cases on Elective Operation Theatre List - Muhammad Kashif Bashir, Jamshaid Javed, Rubab Ameer, Hamna Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To establish factors resulting in postponement of patients on elective operation theatre list. Material and Methods: The design of this study was Prospective observational study. This study was conducted at department of pediatric surgery King Edward medical university / Mayo hospital Lahore from October 2019 to October 2021. Elective operation theatre list is made one day before elective operation theatre list. Patient information regarding diagnosis and possible cause of postponement was noted on prescribed proforma. Results: The total number of scheduled cases was 3900 (Average of 15 cases per list). Out of these 3545(90.9%) patients got operated while the remaining 355(9.1%) patients were postponed due to different reasons. Thus, the overall rate of postponement was 1.36 patients per list. Out of these 355(n=1) postponed cases, 160(45.1%) cases were cancelled due to operation theatre related reasons like shortage of surgical instruments, medicine and linen. 120(33.8%) patients were postponed due to reasons directly related to patients and parents. 65(18.3%) cases postponed due to shortage of man power. 10 (2.8%) patients, were postponed due to unscheduled holiday and power breakdown of operation theatre. Conclusion: Postponement of patients from elective surgery list is avoidable. Timely optimization and team work can reduce these issues.